New insights on the Andean-related subcontinental lithospheric mantle and evidence of Sr-Nd decoupling - Conceicão, R. V. (2003)
The subcontinentallithospheric mande, assumed to be the portion of the lithosphere below the Mohorovicic discontinuity and above the asthenosphere, can be defined in terms of its chemical, thermal, seismic and/or mechanical properties. Simple petrological and chemical models have been suggested for the bulk composition and mineralogy of the oceanic lithospheric mande (Ringwood, 1982). However, for the understanding of the subcontinental lithospheric mande composition and mineralogy, difficulties have arisen due to its long-term evolution and processes responsible for continuous changes of its composition (McDonough, 1990). Sorne of these processes have been described as metasomatism. Metasomatism is defined as the percolation of fluids or melts through the mande inducing its compositional, and in sorne cases mineralogical, modifications. The rnetasomatie agent has been attributed to products derived either from the asthenosphere undemeath or from the subducted crust in compressive regimes.